Romance Formula in Novel Twilight by Stephenie Mayer: Popular Literature Studies - Syifa Dilivia Raharjo (Universitas Andalas, 2023)
Popular literature is become a growing phenomenon in the world of literature, it’s making popular literature one of the literary studies. There are several types of literary works that can be categorized as popular literature. Novels are one type of literary work that is favored by many people. A novel can be categorized as a popular novel if there are many readers who buy the novel to read it. One of the popular novels is a novel entitled Twilight by Stephenie Mayer which is a romance genre. The Twilight novel is one of the novels that has a world best seller label, this means that the novel is favored by many people. Therefore, this study discusses the romance formula contained in the Twilight novel. Thus, formulaic literary theory was used in the study. The theory used is the theory of John G. Cawelti. According to Cawelti, the conventional patterns play an important role in the popularity of a literary work. Therefore, the analysis of formulas in a literary work can prove why the work is popular. The type of this research used is descriptive and the method used is qualitative method. This research resulted in the Twilight novel having a formulaic type like what Cawelti expressed: the presence of heroes and heroins, the hero is portrayed as perfect, heroin characters are portrayed as ordinary, and have a happy ending. The conclusion obtained from this study is that the romance formulas in the Twilight novels affect the popularity of the novel.